Requerimientos on line – servicios de internet para atención de requerimientos y servicios al cliente - Dominguez Menoscal, Lidia Florinda (2009)
Our thesis is an important tool for the company INTERAGUA in the area of customer service, improving customer service quality, allowing decongest customer points and allows to control organized in income, allocation and completion of paperwork, Additional to this also allows the classification and distribution requirements. Applying supervisory controls most important phases, with a platform for easy access and security controls for the client's income either through personally requested key to the entity. The result will expedite the process and outcomes of customer requirements to the entity.